Modeling and Analysis on Teacher-Student Relationship - Li Xu; Qi Yang (Discrete Dynamics in Nature and Society)
Although the teacher-student relationship has been addressed in some studies, the cooperation or reciprocal relations between teachers and students have not been explored sufficiently. In this paper, a difference equation model is applied to express the relationship, stability analysis at the positive steady state of the discrete model is done to verify that the performance output is not empty, and hypothesis testing is conducted to show the validity of the model by means of sample data from a college. Then some reasonable suggestions are proposed to improve the performance output of teachers and students.